2015
DOI: 10.1002/ajmg.a.37286
|View full text |Cite
|
Sign up to set email alerts
|

Autism spectrum disorder in Prader–Willi syndrome: A systematic review

Abstract: Prader-Willi syndrome (PWS) is a rare genetic disorder that results from lack of expression of paternally-derived genes on chromosome 15q11-13; caused by a deletion (DEL), uniparental disomy (UPD), or a rare imprinting center defect. PWS is associated with a distinct behavioral phenotype that in some respects overlaps with autism spectrum disorder (ASD), a neurodevelopmental disorder characterized by restricted or repetitive behaviors (RRBs) and social-communication impairment. The goal of this review was to (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
95
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 56 publications
3
95
1
1
Order By: Relevance
“…This is a marked contrast to the 27% of PWS cases diagnosed with ASD. 13 Notable cognitive behavioral characteristics were described as being impulsive, compulsive, varying degrees of stubbornness, and being manipulative. Detailed neuropsychological phenotyping would be warranted to further delineate the behavioral phenotypes of individuals with MAGEL2 loss-of-function.…”
Section: Discussionmentioning
confidence: 99%
“…This is a marked contrast to the 27% of PWS cases diagnosed with ASD. 13 Notable cognitive behavioral characteristics were described as being impulsive, compulsive, varying degrees of stubbornness, and being manipulative. Detailed neuropsychological phenotyping would be warranted to further delineate the behavioral phenotypes of individuals with MAGEL2 loss-of-function.…”
Section: Discussionmentioning
confidence: 99%
“…The number of participants with PWS beyond the cut-off value of 15 for an autism spectrum disorder (ASD) was 50%, which is higher than generally assumed. According to most recent estimations of Bennet et al, 26.7% of persons with PWS meet the criteria for ASD [42]. Furthermore, our autism screening scores were correlated with the CBCL total problems T scores in the entire study group.…”
Section: Discussionmentioning
confidence: 98%
“…Notably, previous research in non-PWS samples indicates that both parent reports and observational data are essential to valid diagnostic assessment for ASD [22]. In a recent systematic review of ASD in PWS, Bennett et al [3] reported that most studies investigating ASD in PWS are based on single measures, with parent reports more common than observational assessment (i.e., ADOS-2). Given that parent reports may be less resource-intensive and require less specialized training, they may be more feasible to administer in a clinical program serving a rare population such as PWS.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the prevalence of ASD in PWS has been estimated at 26.7% based on exceeding clinical cut-points on relevant ASD assessments [3]. Also, ASD in the UPD genetic subtype (35.3%; two maternal copies of chromosome 15 present) is almost twice as common as in the DEL subtype (18.3%) [3]. This may be partially due to a genetic finding that overexpression of chromosome 15 is associated with higher rates of ASD [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation